Changes in weed biodiversity in onion and carrot agrocenoses in the Skierniewice region from 1995 to 2024 - Golian, Joanna; Anyszka, Zbigniew; Dobrzański, Adam (Journal of Plant Protection Research, 2026)
Observations of weed infestation were carried out in onion and carrot crops from 1995 to 2024 in the Skierniewice region. Weed infestation was assessed on unsprayed fields based on weed numbers determined between 29 and 78 days after sowing. Based on species composition and weed abundance, the weed community structure was determined using the Shannon-Wiener species diversity index (H), Simpson's dominance index (SI), Pearson correlation coefficients (r) and Multiple regression. Weed populations in onion and carrot exhibited substantial year-to-year variability and no long-term trends. The most abundant species in onion and carrot were Capsella bursa-pastoris, Thlaspi arvense, Chenopodium album, and Galinsoga parviflora. In onion, an increasing tendency in the number of Galinsoga parviflora Capsella bursa-pastoris, Thlaspi arvense, and Echinochloa crus-galli was observed, while the number of Chenopodium album plants showed a tendency to decrease. In carrot, an upward trend in the populations of Capsella bursa-pastoris and Chenopodium album was observed, although annual fluctuations remained substantial. The climatic effects on weed communities were weak and inconsistent across crops, explaining only a small weed variation and indicating that long-term weed dynamics are shaped primarily by non-climatic factors.